Lexical borrowings as a means of conveying foreign concepts in Ukrainian mass media - Vozniak, Ihor (Lviv Polytechnic Publishing House, 2016)
The article deals with the problem of lexical borrowings from English into Ukrainian in mass media discourse. Some theories on this matter and their prominent representatives are mentioned. Stylistic features of loan words usage are discussed. Examples of borrowings which imply cultural background are given.
Keywords: lexical borrowing; mass media discourse; cultural background; stylistics; language interactions